2018
DOI: 10.1186/s40645-018-0178-5
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal march patterns of the summer rainy season in the Philippines and their long-term variability since the late twentieth century

Abstract: This study investigates the seasonal march patterns of rainfall in the Philippines from 1951 to 2012 and their long-term variability. In order to clarify the dominant patterns in the seasonal march of rainfall, an empirical orthogonal function (EOF) analysis was applied to pentad rainfall data of 30 stations. For the first EOF mode (EOF1), we obtained a pattern related to the summer rainy season. We then applied cluster analysis to the time coefficients of EOF1 in each year to classify the seasonal patterns of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…One pentad later in P28 (Figure 2e), the whole wind system in the north of 10 N abruptly changed from easterly to westerly, which clearly marks the onset of summer SW monsoon wind regime in the Philippines. The timing is almost the same as the first transition of the Asian monsoon (Matsumoto, 1997;Hsu et al, 1999;Ueda, 2005), or the climatological monsoon onset of the Philippines defined by Akasaka (2010), Akasaka et al (2007Akasaka et al ( , 2018, and Moron et al (2009). In the east of Luzon Island is the southwestern periphery of the WNPSH anticyclonic flow, and the convergence between the southwesterly and southeasterly is located in the east of the northern Philippines, while it is over Visayas.…”
Section: Climatological Features Of Rainfall and Low Level Circulationmentioning
confidence: 58%
See 2 more Smart Citations
“…One pentad later in P28 (Figure 2e), the whole wind system in the north of 10 N abruptly changed from easterly to westerly, which clearly marks the onset of summer SW monsoon wind regime in the Philippines. The timing is almost the same as the first transition of the Asian monsoon (Matsumoto, 1997;Hsu et al, 1999;Ueda, 2005), or the climatological monsoon onset of the Philippines defined by Akasaka (2010), Akasaka et al (2007Akasaka et al ( , 2018, and Moron et al (2009). In the east of Luzon Island is the southwestern periphery of the WNPSH anticyclonic flow, and the convergence between the southwesterly and southeasterly is located in the east of the northern Philippines, while it is over Visayas.…”
Section: Climatological Features Of Rainfall and Low Level Circulationmentioning
confidence: 58%
“…As for the rainfall increase in the Indochina Peninsula, Kiguchi and Matsumoto (2005) and Kiguchi et al (2016) attributed to the influence of mid-latitude westerly trough to the occurrence of rainfall before the monsoon circulation onset. On the other hand, Akasaka (2010) and Akasaka et al (2007Akasaka et al ( , 2018, and Moron et al (2009) did not present such discrepancy between the rainy season onset and monsoonal wind changes. In order to investigate the reason for this discrepancy, we have plotted the similar time-latitude sections of rainfall and wind in each year, as in Figure 2, and found that in 9 years (1999,2000,2001,2004,2005,2007,2008,2009, and 2011) the increase of rainfall occurs earlier than the wind shift from easterly to westerly, while in other years, they change almost simultaneously.…”
Section: Spatial Contrasting Features Of Rainfall and Low-level Cirmentioning
confidence: 74%
See 1 more Smart Citation
“…In particular, the rainy season over the western coast occurs from May to September (summer monsoon) and followed by a dry season, while the eastern coast experiences its rainy season from November to March (winter monsoon) [18][19][20][21]. Recently, a number of studies found long-term changes in the rainfall and temperature of the Philippines [19,[22][23][24][25][26][27][28]. For example, Cruz et al [25] found decreasing rainfall trends during the summer monsoon season (June to September) in stations located over the western coast of the country from 1961-2010.…”
Section: Introductionmentioning
confidence: 99%
“…(1) While there are many studies that have investigated the variability (i.e., long-term trends and interdecadal shift) of the summer monsoon rainfall of the Philippines [19,[22][23][24][25][26][27][28][29], the variability of the winter monsoon rainfall has received less attention. According to Assuncion and Jose [30], the winter monsoon accounts for 38% of the total annual rainfall in the Philippines, while the summer monsoon accounts for about 43%, suggesting that the rainfall contribution of the winter monsoon is equally important with that from the summer monsoon.…”
Section: Introductionmentioning
confidence: 99%